2013
DOI: 10.1523/jneurosci.2546-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Early Auditory Processing in Area V5/MT+ of the Congenitally Blind Brain

Abstract: Previous imaging studies of congenital blindness have studied individuals with heterogeneous causes of blindness, which may influence the nature and extent of cross-modal plasticity. Here, we scanned a homogeneous group of blind people with bilateral congenital anophthalmia, a condition in which both eyes fail to develop, and, as a result, the visual pathway is not stimulated by either light or retinal waves. This model of congenital blindness presents an opportunity to investigate the effects of very early vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 35 publications
3
63
0
1
Order By: Relevance
“…The latter region is known to support motion processing, irrespective of the sensory modality of input (17,69,70). Cross-modal activations of the V5/MT area by both moving and static auditory stimuli were previously observed in blind persons (17,(71)(72)(73). Increased activation of this region relative to hearing subjects was also observed in deaf subjects during their perception of peripheral visual motion (74), a function that is known to be supported by the auditory cortex in the deaf (25,26,36).…”
Section: Discussionmentioning
confidence: 91%
“…The latter region is known to support motion processing, irrespective of the sensory modality of input (17,69,70). Cross-modal activations of the V5/MT area by both moving and static auditory stimuli were previously observed in blind persons (17,(71)(72)(73). Increased activation of this region relative to hearing subjects was also observed in deaf subjects during their perception of peripheral visual motion (74), a function that is known to be supported by the auditory cortex in the deaf (25,26,36).…”
Section: Discussionmentioning
confidence: 91%
“…It would also be interesting to examine the anatomy and physiology of neurons in the thalamus and somatosensory cortex in Cdx1-Cre;Fz3 CKO/− mice to explore the fate of territories that normally process somatosensory information from the trunk and limbs. One might anticipate that there would be a large scale remapping of these territories analogous to the remapping of visual cortex in humans or animals that are congenitally blind (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…We found that in blind individuals, a subset of early visual cortices is active while solving math equations, and this activity scales with mathematical difficulty. Much evidence has documented responses to auditory and tactile stimuli in visual cortices of congenitally blind individuals (22)(23)(24)(25)(26)(27). The mechanisms and the scope of functional reorganization in cross-modal plasticity remain debated (43).…”
Section: Increased Functional Connectivity Between Visual Cortices Anmentioning
confidence: 99%
“…In blindness, "visual" areas of the brain are colonized by nonvisual functions. These occipital areas respond to auditory and tactile stimuli, a phenomenon termed cross-modal plasticity (22)(23)(24)(25). Some of these plastic responses appear to be related to higher-cognitive functions-most prominently, language processing and verbal memory (23,(25)(26)(27).…”
mentioning
confidence: 99%